Nursing personnel management during COVID-19 pandemic: An exemption trend in view of health reasons - Sharma, Sruti; Dhaliwal, Navneet; Bhadada, Sanjay; Kumar, Ashok; Sangat, Sumit Kumar; Pandey, Navin (Frontiers in Public Health, 2022)
In Covid 19 pandemic, healthcare system faced unprecedented challenges with increased number of patients and limited resources. Managing nursing resource was a major challenge for hospital administration. They had to be on the frontline but their safety was of paramount importance. Aim: This study aims to analyse the measures taken for the management and effective engagement of nursing personnel for deployment in covid area of the hospital and the exemption trend based on their health status. Methodology: A retrospective cross sectional descriptive study was carried out to analyze the requests of nursing staff received for exemption of duty in covid patient care areas. These requests were categorized and examined by the medical board constituted for this purpose. Microsoft excel was used to interpret the results. Results: The study evaluated the health reasons among nursing officers on the basis of which exemption was given for deployment of nursing officers in covid areas. There were mostly medical reasons (91.1%) and few personal reasons (8.77%). Majority suffered from diseases affecting two or more than two specialties. Out of 376 applications, 223 were exempted, 81 were not exempted, 13 were given short term exemption while 26 were shifted to administrative assignments. Thirty three staff were referred to an appropriate forum.